A novel numerical method of transient temperature simulation for a HVAC room. (October 2018) - Lv, Qian; Yu, Xiaoling; Ding, Yifeng; Yang, Shuo; Jiang, Liming; Jia, Xiaofei; Jin, Liwen
Abstract: To solve the severe air pollution problem, Chinese government presented proposals of the electrical heating substitute of the coal combustion for warm. The heat pump is the most economic electrical heating utility. From the start to steady operation of a heat pump, its electrical power is changed with the transient temperature rising of the heated room. Thus, the study of the transient room temperature rising is crucial to evaluate electrical power change of the heat pump. This paper presented a novel numerical simulation method to simulate transient temperature rising of a HVAC room. In this method, velocity of hot air blown off by a fan coil was not constant as usually was, and it was changed with the transient room temperature. This novel simulation method can simulate the real room heating process. The 3-dimensional transient room temperature model was built in a commercial software Fluent. Velocity of hot air blown off by a fan coil was the boundary condition of the model. Hot air velocity was first calculated by the lumped parameter method (LPM), and then it was applied as initial boundary condition of the transient room temperature model. Using this method, the transient temperature rising of a HVAC room was simulated under different outdoor temperatures. Before the heat pump started, the room temperature was assumed to be 3℃ higher than the outdoor temperature. The room was heated until its temperature reached the required temperature. Then, the heat pump steps into the operation state. The time-history of the room temperature from start to steady operation of the heat pump are obtained and analyzed. The results show the novel method can expedite the computation speed. For each time step, the results converged only after 2 3 iterations.